(untitled) - Mobley, R. Keith (New York, 2008)
This definitive resource focuses on proven best practices for maintenance, repair, and overhaul (MRO), inventory management, root-cause analysis, and performance management.
Keywords: Bảo dưỡng nhà máy,Plant maintenance; Sổ tay, hướng dẫn sử dụng, vv,Handbooks, manuals, etc